Lokalna organizacja turystyczna a zarządzanie turystyką w regionie - Gryszel, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article presents organizational background for local tourist organizations and their influence on tourist economy management in a region. The tasks of the Polish Airlines LOT office are characterized as well as the manner of its organization and financing. On the basis of conducted research an assessment of selected local tourist organizations functioning in Poland is performed. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 66-76